PENGARUH MODEL PEMBELAJARAN JEROLD E.KEMP TERHADAP HASIL BELAJAR MANAJEMEN KEUANGAN PADA PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UMSU TAHUN AKADEMIK 2019/2020 - Fatmawarni Fatmawarni; Dinda Nurazli Chania (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
The purpose of this study was to determine the effect of the Jerold E. Kemp learning model on student learning outcomes in the Financial Management course in the Accounting Education Study Program, FKIP UMSU, Academic Year 2019/2020. The problem in this study is the low learning outcomes of students in Semester 6 in class A in the morning, amounting to 25 students who were sampled with the sampling technique using nonprobability sampling with a class type consisting of one class or total sampling. The research instrument used was a test, which first tested the validity of the questionnaire and its reliability. This study used the Liliefors test to determine the normality of the learning outcome data and the F test to determine the homogeneity of the data. Based on the results of data analysis, it is known that the results of the calculation of the hypothesis test tcount = 2.34. Furthermore, the results of tcount is compared with a significant level of a = 0.05 with dk = n-2 = 38 obtained ttable = 2.06866 if tcount> ttable then H_a is accepted, meaning that that there is a significant influence of Jerold E. Kemp's learning model on student learning outcomes in the Financial Management course.